Polyamines as Modulators of Salt Tolerance in Rice Cultivars - Krishnamurthy, R. (1989)
The effect of NaCl on the endogenous levels of diamine, putrescine and polyamines, spermidine and spermine, was studied in the shoot system of salt-tolerant and salt-sensitive lines of rice (Oryza sativa L.) cultivars during three growth stages. Salt stress increased the levels of diamine and polyamine in varying degrees among nine rice cultivars investigated. Salt tolerant AU1, Co43, and CSC1 were effective in maintaining high concentrations of spermidine and spermine, while the content of putrescine was not significantly altered in all the growth stages when plants were exposed to salinity. The salt sensitivity in rice was associated with excessive accumulation of putrescine and with low levels of spermidine and spermine in the shoot system of salt-sensitive cultivars Co36, CSC2, GR3, IR20, TKM4, and TKM9 under saline condition. One of the possible mechanisms of saline resistance was observed to be due to the highly increased polyamines against the low increase in diamines. Alternatively, the salt sensitivity could be due to high increase of diamines and an incapacity to maintain high levels of polyamines.